Artificial Intelligence and Financial Regulation in Indonesia’s Islamic Banking: a Systematic Literature Review - Muhammad Bashri Bas; Rika Febby Rhamadhani; Rasmi Nur Anggraeni; I Putu Edi Darmawan; Phatra Anggana Djuri (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The integration of Artificial Intelligence (AI) into Islamic financial products marks a transformative shift in the global financial ecosystem, particularly in Indonesia, where Islamic finance constitutes a vital pillar of the national economy. This study conducts a systematic literature review to explore the evolving intersection between AI technologies and Islamic financial systems, with a specific focus on implications for Indonesia’s regulatory and institutional landscape. Employing a qualitative-descriptive approach, the study examines the types, phases, and functional characteristics of AI, as well as the operational principles and structures of Islamic financial products, including murabaha, mudarabah, and sukuk. Findings indicate that AI has the potential to significantly improve operational efficiency, enhance transparency, facilitate real-time decision-making, and expand financial accessibility among underserved Muslim populations. However, the integration of AI also raises important concerns, particularly regarding Shariah compliance, data ethics, algorithmic bias, and regulatory readiness. The study highlights gaps in existing regulatory frameworks, including the lack of AI-specific guidelines within the current Islamic finance governance structures. To address these challenges, the paper proposes a set of policy recommendations, such as developing Shariah-aligned AI standards, enhancing collaboration between regulators and fintech developers, and fostering capacity-building among Islamic finance professionals. By ensuring that AI implementation aligns with Islamic ethical values, Indonesia can position itself as a leader in sustainable, inclusive, and innovation-driven Islamic finance in the digital era.